Evaluation of 3D printing inks and printed edible spoons made from food processing side streams - Stachnik, Marta; Kulju, Eija; Laaksonen, Oskar (Elsevier, 2026)
3D printing technology was used to develop prototypes of edible spoons from side streams of food and beverage production. All ink formulations were based on brewer's spent grain and supplemented with one of the following: apple or berry pulp, or powdered seeds from black currant or sea buckthorn. The printability of the food ink was assessed through rheological measurements, while the spoons were tested for their water and oil absorption, and water solubility and sensory quality. Inks exhibited elastic behavior at rest, becoming viscous under shear (phase shift angle from 14° to 80°). Both storage (G′) and loss (G″) moduli showed significant recipe-dependent variations. The recovery rate was notably low which was further reflected in the sagging of the ink after the print. All spoons nearly doubled their weight when submerged in water, but not in oil – on average 20 % increase in weight. Spoons made only with spent grain had significantly higher water solubility than other recipes. Spoons made with addition of berry pulp received the highest ratings, on average 6 out of 9 in hedonic scale; while other spoons were rated on average 5 out 9. When used to consume yogurt, the spoons did not alter its flavor. The texture of all spoons was considered appealing, with the 3D printing layers being either imperceptible or pleasant.